Transformasi Iman: Membentuk Warga Jemaat yang Berdampak - Artariah Artariah; Yesica Tanjung; Megawati Manullang (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
Faith transformation is a spiritual process that changes the lives of believers so that they become more Christ-like, both internally and externally. This paper discusses the importance of a living and dynamic faith that has a real impact in daily life. Churches and church leaders have a strategic role in the development of the congregation through spiritual education, social services, character building, and the utilization of technology. The faith transformation model involves a continuous spiritual journey that starts from awareness of God's call, repentance, to becoming an agent of social change. The impact of faith transformation includes individual spiritual maturity, contribution to church ministry, and positive influence on the wider community. With a purposeful strategy, a transformed congregation can become a channel of God's love that blesses the family, the church, and the world.